INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE OF THE COMPANY - Maharani, Nila Bilqis; Faisal, Faisal (Jurnal Reviu Akuntansi dan Keuangan)
This study tests the relationship between intellectual capital and corporate financial performance of Indonesian companies. 63 companies of six industrial sectors listed on Bloomberg Database in 2015-2017 were selected as a sample. The descriptive statistics, Spearman’s correlation and non-parametric Kruskall-Wallisand Mann-Whitneytests were used to analyze the relationship between dependent (financial performance) and independent (intellectual capital) variables. Our findings show that intellectual capital provides a positive contribution effect on corporate financial performance. Consistent with resource- based theory, this finding suggests that intellectual capital is a strategic resource that can generate a value for company to gain a superior performance and competitive advantage.